THE INFLUENCE OF READING HABITSAND READING STRATEGIES ON STUDENTS’ READING COMPREHENSION ATJUNIOR HIGH SCHOOL 1 IN THE DISTRICT OFBENAI-KUANSING - Tengku Syamsinar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
CIRC is a cooperative learning program that involves a series of activities derived from research on reading comprehension and writing skill. Students work in four-member heterogeneous learning teams. After the teacher introduces a story from a basal text or trade book, students work in their teams on a prescribed series of activities relating to the story. In this research, two classes were involved; one class as the experimental group, which was treated by using CIRC method and another one as control group was taught without using CIRC method. For both experimental and control groups, pre-test and post-test were administered to the students. The data were analyzed by using statistical analysis. To know the result whether it was be statistically significant, it was analyzed by using t-test. This study investigated the effect of using cooperative integrated reading and composition (circ) method on students’ reading comprehension and writing skill. Data the research were collected from 30 students of SMAN 1 Rimba Melintang. The findings showed Reading Comprehension that the average score of the pre-test was 50.83 and post-test was 76.17. and findings showed Writing Skill that the avearge score of the pre-test was 62.63 and post-test was 74.67.Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. There was significant effect of using cooperative integrated reading and composition (CIRC) method on students’ reading comprehension and writing skill at SMAN 1 Rimba Melintang. Keywords: Cooperative integrated reading and composition (CIRC) Reading Comprehension,and Writing Skill.